Was higher education a major channel through which the US became an economic superpower in the 20th century? - Adam Cook; Isaac Ehrlich (Asian Development Bank Institute (ADBI), 2018)
This paper offers a thesis for why the United States (US) overtook the United Kingdom (UK) and other European countries in the 20th century in both aggregate and per capita GDP as a case study of recent models of endogenous growth, where "human capital" is the engine of growth. By human capital we mean an intangible asset, best thought of as a stock of embodied and disembodied knowledge comprising education, information, entrepreneurship, and productive and innovative skills, which is formed through investments in schooling, job training, and health as well as through research and development projects and informal knowledge transfers (cf. Ehrlich and Murphy 2007). The conjecture is that the ascendancy of the US as an economic superpower in the 20th century owes considerably to its faster human capital formation relative to that of the UK and "old Europe." This paper assesses whether the thesis has legs to stand on through both stylized facts and a supplementary quasi-experimental empirical analysis. The stylized facts indicate that the US led other major developed countries in schooling attainments per adult population member, beginning in the latter part of the 19th century and lasting throughout the 20th century, especially at the secondary and tertiary levels. The quasi-experimental analysis constitutes the first attempt to test the hypothesis that the US's ascendancy to a major economic power stems largely from the impact of the first Morrill Act of 1862, which launched the public higher education movement in the US through the establishment of land grant colleges and universities across the nation during the latter part of the 19th century. The higher education movement appears to have spearheaded a higher long-term rate of growth in per capita income in the US relative to the UK and other major European countries.
Keywords: H1; I2; N1; N3; O0; O4; C21; 330; human capital; endogenous growth; Morrill Act; higher education; treatment effects; US